2012
DOI: 10.3354/ab00433
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the transport of broadcast coral larvae among the Southern Islands of Singapore

Abstract: Singapore's coral reefs have experienced significant anthropogenic impacts for at least 4 decades. Ongoing reef restoration efforts, however, may not be sustainable if there is no natural coral recruitment. Knowledge of coral reef connectivity, which can be identified using hydrodynamic-advection and individual-based models, can help inform reef management decisions. Here, a 2-dimensional, hydrodynamic, flexible mesh model (MIKE 21 FM) coupled with a Lagrangian particle-tracking module was used to simulate lar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 71 publications
(90 reference statements)
2
47
0
5
Order By: Relevance
“…If this is the case, the short time scales of dispersal shown here are important because both larval density ( Figure 6) and recruitment success decrease quickly with time and distance (Sammarco and Andrews, 1988) due to mixing and horizontal dispersion (Wolanski et al, 1989;Oliver et al, 1992). It has been demonstrated (Andutta et al, 2012;Tay et al, 2012) that reefs and islands in close proximity often result in decreased flushing and thus more exposure time in areas where settlement can occur successfully; these features are generally not captured with large-scale models (Vaz et al, 2013;Wood et al, 2014). In this case, the flushing between islands appears to be somewhat offset by areas in the lee of the high islands that result in increased retention that was not captured in previous modeling studies (Andutta et al, 2012;Tay et al, 2012) where topographic steering of winds was not a factor.…”
Section: ) and Genetic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…If this is the case, the short time scales of dispersal shown here are important because both larval density ( Figure 6) and recruitment success decrease quickly with time and distance (Sammarco and Andrews, 1988) due to mixing and horizontal dispersion (Wolanski et al, 1989;Oliver et al, 1992). It has been demonstrated (Andutta et al, 2012;Tay et al, 2012) that reefs and islands in close proximity often result in decreased flushing and thus more exposure time in areas where settlement can occur successfully; these features are generally not captured with large-scale models (Vaz et al, 2013;Wood et al, 2014). In this case, the flushing between islands appears to be somewhat offset by areas in the lee of the high islands that result in increased retention that was not captured in previous modeling studies (Andutta et al, 2012;Tay et al, 2012) where topographic steering of winds was not a factor.…”
Section: ) and Genetic Methodsmentioning
confidence: 99%
“…Insolation-driven heating and nocturnal cooling of the islands cause the general Trade wind speeds in the vicinity of the islands to vary from almost negligible at night to more than 15 m s −1 in the afternoon, compared to about 5 m s −1 in the open ocean. These relatively rapid diurnal variations in wind speed result in a very thin (<1 m) winddriven surface layer (Storlazzi et al, 2006b) that constrains positively-buoyant particles, such as coral larvae during their planktonic dispersal stage (Storlazzi et al, 2006a), varies greatly over small spatial and temporal scales, and is not captured in larger-scale oceanographic models (Tay et al, 2012;Vaz et al, 2013;Wood et al, 2014). The wave climate in Maui Nui during the period of coral spawning in the boreal summer is dominated by two wave regimes: northeast Trade wind waves and Southern Ocean swell (Moberly and Chamberlain, 1964).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Despite exposure to continued anthropogenic pressure, the remaining reefs remain vigorous in terms of growth [4] , reproduction [5] and recruitment. There is no indication of scleractinian coral species decline [6] and modelling studies showed that the reefs are self-seeding [7] with adequate larval supply. New challenges are posed by climate change impacts.…”
Section: Introductionmentioning
confidence: 99%
“…They are considered viable despite the continued anthropogenic impacts to the marine environment, as annual coral mass spawning events which occur with a high degree of predictability contribute significantly to the self-seeding of Singapore's reefs [13]- [15]. The overall approach to reef restoration since the 1990s is aimed at circumventing the problems of high sedimentation and destabilized substrate, and comprises physical (e.g.…”
Section: Introductionmentioning
confidence: 99%